2020
DOI: 10.1002/ajoc.202000077
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Synthesis of Heteroarylselenyl Esters from Diheteroaryl Diselenides and Acid Fluorides

Abstract: A rhodium complex catalyzed C−Se bond formation between diheteroaryl diselenides and acid fluorides in the presence of triphenylphosphine to provide heteroarylselenyl esters in good yields. The reaction was applicable to five‐ and six‐membered heteroaryl compounds. The heteroarylselenyl esters can be used as heteroaryselenating reagents in the synthesis of heteroaryl selenides, as shown by a platinum‐catalyzed addition reaction with 1‐octyne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…More recently,Y amaguchi reported ad ifferent approach for the synthesis of selenoesters. [49] The synthetic strategy was based on the use of ar hodium complex that catalyzes the formationo fC ÀSe bonds, throught he reaction between heteroaryl diselenides and acyl fluorides, in the presenceo fP Ph 3, to provide hetero-arylselenyl esters in good yields. Thus, through the use of derivatives of pyridine, pyrimidine and thiophene The formation of selenoesters occurs as described in the catalytic cycle illustrated in Figure 4.…”
Section: Synthesis Of Selenoesters: Miscellaneous Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently,Y amaguchi reported ad ifferent approach for the synthesis of selenoesters. [49] The synthetic strategy was based on the use of ar hodium complex that catalyzes the formationo fC ÀSe bonds, throught he reaction between heteroaryl diselenides and acyl fluorides, in the presenceo fP Ph 3, to provide hetero-arylselenyl esters in good yields. Thus, through the use of derivatives of pyridine, pyrimidine and thiophene The formation of selenoesters occurs as described in the catalytic cycle illustrated in Figure 4.…”
Section: Synthesis Of Selenoesters: Miscellaneous Methodsmentioning
confidence: 99%
“…More recently, Yamaguchi reported a different approach for the synthesis of selenoesters [49] . The synthetic strategy was based on the use of a rhodium complex that catalyzes the formation of C−Se bonds, through the reaction between heteroaryl diselenides and acyl fluorides, in the presence of PPh 3, to provide hetero‐arylselenyl esters in good yields.…”
Section: Synthesis Of Selenoestersmentioning
confidence: 99%
“…The presence of triphenylphosphine was crucial for the oxidation of selenol to the corresponding diselenide. [180] Acyl chlorides were also adopted for preparing organoselenyl esters from diorganyl diselenides. In one article, organoselenyl esters 127 were prepared by the cross-coupling reactions catalyzed by CoCl 2 • 6H 2 O involving diaryl, dialkyl diselenides, alkyl, and aryl acyl chlorides (Scheme 120).…”
Section: Diorganyl Diselenides Promoting Cross-coupling Reactionsmentioning
confidence: 99%
“…The studies indicated that the reaction of diorganyl diselenides with acyl fluorides showed better results when conducted in the presence of a catalytic amount of RhH(PPh 3 ) 4 , dppe as the ligand, triphenylphosphine, in THF as the solvent. The presence of triphenylphosphine was crucial for the oxidation of selenol to the corresponding diselenide [180] . Acyl chlorides were also adopted for preparing organoselenyl esters from diorganyl diselenides.…”
Section: Diorganyl Diselenides Promoting Cross‐coupling Reactionsmentioning
confidence: 99%
“…Rhodium-catalyzed reactions of disulfides can be applied to diselenides (Scheme 6) [38]. Bis(2-pyridyl) diselenide and 1-adamantanecarbonyl fluoride were reacted in the presence of RhH(PPh 3 ) 4 (2.5 mol%) and dppe (5 mol%) in refluxing chlorobenzene, and 1-adamantanecarbonyl 2-pyridylselenoester was obtained in 88% yield.…”
Section: Substitution Reactions Of Thioestersmentioning
confidence: 99%